Development of a quiz taker using software engineering tool - Dey, Amit Kumar; Biswas, Moloy Ranjan; Kabir, A.M.M. Shahriar (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.